Answer:
Option 2: (1, 0) and (0, -5)
Step-by-step explanation:
Let's solve this system of equations using the elimination method.
Start by labelling the two equations.
5x -y= 5 -----(1)
5x² -y= 5 -----(2)
(2) -(1):
5x² -y -(5x -y)= 5 -5
Expand:
5x² -y -5x +y= 0
5x² -5x= 0
Factorise:
5x(x -1)= 0
5x= 0 or x -1= 0
x= 0 or x= 1
Now that we have found the x values, we can substitute them into either equations to solve for y.
Substitute into (1):
5(0) -y= 5 or 5(1) -y= 5
0 -y= 5 or -y= 5 -5
y= -5 or -y= 0
y= 0
Thus, the solutions are (0, -5) and (1, 0).
Answer:
f ○ g(x) = x and g ○ f(x) = x is the correct composition
Step-by-step explanation:
INVERSE FUNCTIONS: Two functions are said to be inverse of each other if for every y = f(x), there exists a function g(x),
such that x =
= g(y)
Now, here if we need to show tha two functions f(x) and g(x) are inverse functions of each other , then show that for every x:
1. f o g(x) = f(g(x))= x
2. g o f(x) = g(f(x)) = x
If any two functions satisfy these two conditions, then they are inverse of each other.
Answer:
y=-1
Step-by-step explanation:
yeah-ya...... right?
60% = 0.6
12 / 0.6 = 20
answer 12 is 60% of 20